Potensi Penerbitan Green Sukuk Daerah Dalam Pembiayaan Infrastruktur Berkelanjutan di Kalimantan Tengah - Suherman, Suherman; Kristina, Parista; Natalia, Desi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Sustainable development in Indonesia is increasingly important to address complex environmental and social challenges. The goal of this development is to address contemporary requirements without compromising the prospects of future generations. Indonesia has adopted the Sustainable Development Goals (SDGs) as a framework, but its achievement faces various challenges, such as regional inequality and lack of coordination between stakeholders. Collaboration Collaborative interactions between government entities, community institutions, and the private sector are essential to ensure this success. Green Sukuk has emerged as an innovative financial instrument that supports environmentally friendly projects and can attract more investors. Despite the positive response, challenges in understanding and regulation still exist. In Central Kalimantan, the issuance of Green Sukuk can fund green projects, but also faces problems of understanding among local stakeholders and regulations that are not yet supportive. Overall, the issuance of Green Sukuk has the potential to increase economic progress and generate new job opportunities. However, it is important to ensure that the projects financed are truly sustainable. Research shows the need for a clear regulatory framework and public education so that the potential of Green Sukuk can be maximized in supporting sustainable development in Indonesia. The method used in this study is qualitative with a Netnography approach and SWOT analysis. Netnography helps researchers understand the social and cultural context that influences people's attitudes towards green sukuk, while LNA SWOT provides an overview of internal and external factors that have the potential to influence the success of sukuk issuance. The results of the study are the potential for Green Sukuk issuance in Central Kalimantan, indicating that this province has abundant natural resources and a policy of commitment to sustainable development which will then increase the opportunity for the ijtihad process to begin immediately, providing a great opportunity to develop a green economy. Although focusing on infrastructure, education, health, and the economy in 2024 is a strategic step, challenges such as the lack of public understanding of Green Sukuk and limited financial infrastructure need to be addressed. Therefore, cooperation between the government, private sector, and the community is very important to create an ecosystem that supports the success of Green Sukuk issuance.